2018
DOI: 10.1063/1.5030588
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of excited-state charge-carrier dynamics in organolead tribromide perovskites

Abstract: Excited-state charge-carrier dynamics governs the performance of organometal trihalide perovskites (OTPs) and is strongly influenced by the crystal structure. Characterizing the excited-state charge-carrier dynamics in OTPs under high pressure is imperative for providing crucial insights into structure-property relations. Here, we conduct in situ high-pressure femtosecond transient absorption spectroscopy experiments to study the excited-state carrier dynamics of CH3NH3PbBr3 (MAPbBr3) under hydrostatic pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…As shown in Figure c, the fast lifetime (τ 2 ) gradually becomes slower before 0.6 GPa and then the lifetime remains almost the same until the phase transition of the sample. Compared with the other literature, it is found that the lifetime in this time range should be related to the Auger recombination of carriers. According to the assignment of Auger recombination, we have carried out the excitation power dependent TA spectroscopy experiment of FAPbBr 3 @SiO 2 NCs at atmospheric pressure. Figure S9 shows the measured B1 kinetic traces at different excitation fluences.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure c, the fast lifetime (τ 2 ) gradually becomes slower before 0.6 GPa and then the lifetime remains almost the same until the phase transition of the sample. Compared with the other literature, it is found that the lifetime in this time range should be related to the Auger recombination of carriers. According to the assignment of Auger recombination, we have carried out the excitation power dependent TA spectroscopy experiment of FAPbBr 3 @SiO 2 NCs at atmospheric pressure. Figure S9 shows the measured B1 kinetic traces at different excitation fluences.…”
Section: Resultsmentioning
confidence: 99%
“…The details for the femtosecond transient absorption apparatus are discussed elsewhere. The femtosecond laser (Coherent Libra, U.S.) source was an all-in-one ultrafast oscillator and a regenerative amplifier. The laser system provided 4 mJ pulses with a repetition rate of 1000 Hz.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Pressure treatment can compress the lattice and tune the electronic structure, which can result in novel physical properties. Several teams used hydrostatic pressure to precisely regulate the compressible perovskite crystal structure. In response to pressure, lead halide perovskites experience changes in the Pb–X bond lengths and the Pb–X–Pb bond angles, allowing one to modulate perovskite structural and electronic properties without the need to adjust the chemical compositions.…”
mentioning
confidence: 99%
“…Investigation of charge carrier dynamics in perovskites is a relatively unexplored area, especially computationally, because it requires unconventional simulation tools, such as those developed in our group. , Such investigations are particularly important because carrier lifetime is one of the key parameters that determine solar cell performance. Recently, investigations of pressure-induced effects in MA and formamidinium (FA)-based lead halide perovskites have uncovered unusual phenomena, associated with structure changes and charge recombination dynamics. ,,, By applying mild pressure, Kong et al have demonstrated that the [PbI 6 ] 4– octahedra in MAPbI 3 undergo substantial distortions, resulting in simultaneous band gap narrowing and carrier lifetime prolongation . Such inverse correlation between the band gap and the lifetime is unexpected because according to the common arguments, such as the energy gap law, lower energy gaps are associated with reduced excited state lifetimes.…”
mentioning
confidence: 99%